Pola Pendidikan Islam Dalam Mewujudkan Keluarga Sakinah - Erlin Indaya Ningsih; Ahmadi (Qolamuna : Jurnal Studi Islam, 2021)
This article will discuss about the pattern of Islamic educationin realizing Prosperous family. The dimensions that need to bedeveloped in children from birth, physical, intellectual, faith,moral, duty, aesthetic and social. All these dimensions areimportant and need to be developed in a way; First maintainmorals and decency ; The elders love the young and guide him,the little respect for the elders and the great. Second; Savingand living a simple, concurrent lifestyle in the face of life, based on the simplicity of life and frugality. Third; Aware of their own defects, because many people are too diligent to see thedisgrace and disfigurement of others, often pointing at others,fingering their fingers at others, but rarely applying them tothemselves.Keywords : Islamic Education , Sakinah Family.